Barreras comerciales: amenazas y oportunidades para las economías en desarrollo (2013)
This essay on international trade barriers is an analysis of the approaches of the authors who for centuries have established the importance of world trade and globalization processes that today are progressing rapidly, making the world an interdependent and interconnected conglomerate of economic, cultural, social and environmental networks. Therefore the role of trade barriers and especially non-tariff barriers (NTBs) have transformed in the trading system as this also changed according to the new challenges posed by economic integration, regardless of the size, shape or nature of countries like Colombia, which is trying to insert itself in a global market more competitive and demanding. This paper analyzed e how trade barriers have played a role that goes beyond the protection of domestic industry, responding to political and macroeconomic interests, trying, these ones, to cover structural weaknesses in the economies of countries in process of economical integration. In the same way, the case of Colombia is observed in order to identify new challenges that must be managed from business tools, such as barriers, in the process of internationalization of its economy, before they become a threat to its structural flaws.